Two-Dimensional MXene (Ti3C2Tx)-based Nano-Photosensitizers for Enhanced Photothermal Ablation of Tumor Cells - Sundramoorthy, Ashok K. (Micro and Nanosystems, 2025)
Cancer remains one of the leading causes of death globally, accounting for approximately one in every six deaths. Traditional cancer therapies, including surgery, chemotherapy, chemoimmunotherapy, and radiation, face numerous challenges and limitations. In this context, we explore the advantages of photothermal therapy (PTT) using two-dimensional (2D) MXene-based nanocomposites for cancer treatment. MXenes, composed of abundant and non-toxic elements, such as titanium (Ti), carbon (C), fluorine (F), and oxygen (O), demonstrate low toxicity and are promising candidates in photothermal cancer therapies. Their ultrathin planar nanostructure, high photothermal conversion efficiency, strong near-infrared (NIR) responsiveness, and chemically modifiable surfaces enhance their therapeutic potential. Recent innovations include the development of folic acid-functionalized Au@c-Ti3C2 nanostructures, a skin-mountable electrostimulation patch (eT-patch), ionic gels containing MXene (Ti3C2Tx), and composite scaffolds made of MXene, collagen, silk fibroin, and quercetin. These MXene-based photosensitive compounds offer efficient targeting and selective treatment of cancer cells, highlighting their significant role in advancing cancer therapies.
Keywords: 2D nanomaterials